About the time I decided to study Letras: perezhivanie and narrative pathways - Lima, Fernando Silvério de; Mendes, Gleisla Thais (The ESPecialist, 2024)
This research investigates the narrative trajectories of four students entering the Letras course. To achieve this, it was considered the cultural-historical concept of perezhivanie, which refers to the emotional experiences that an individual goes through as part of their development, highlighting the influence of the sociocultural context refracted by the subject. The experience in question focuses on the choice of college major, the first memories of language learning, the inclination towards teaching/translation and the decision to take the degree. The results revealed an affective relationship with the field of language since childhood, alongside the presence of encouraging teachers. However, challenges such as professional devaluation and lack of social support were recurrent. Also, learning a new language emerges as an opportunity to vent. In this way, The study seeks to understand the decisive factors in choosing a language major, thus contributing to the improvement of these courses in higher education.